Competition for a temple in Irkutsk’s Studgorodok - Buinov, Alexei; Kazaryan, Armen (project baikal, 2024)
The article contains brief information and a general analysis of the results of the Open All-Russian competition for the development of the best project of the Church of St. Sergius of Radonezh for the Irkutsk campus, the results of which were summed up on November 22, 2023. The article presents a comparative analysis of the winning project elaborated by the creative group of Moscow architects led by Andrey Anisimov and two other projects that reached the final of the competition. The competition reflected the main focus of the creative concepts of modern architects designing Orthodox churches.
Keywords: architectural competition; project of the church; postmodernism; traditional image; Andrey Anisimov; architectural image